Bill of Lading: S.S. Dellwyn
029-0045-001 N.C.L. NOS 10/34 25 CASES SHIPS BISCUITS. 1602 Kilos Shipped in good order and condition by CO-OPERATIVE WHOLESALE SOCIETY Ltd. of LIVERPOOL in and upon the good Steam-Ship called the DELLWYN whereof ELLIOTT is Master for this present Voyage lying in the Port of LIVERPOOL and bound for BARCELONA having liberty to call at any Ports to sail without Pilots and to tow and assist Vessels in all situations. TWENTYFIVE CASES being marked and numbered as per margin; and to be delivered in the like good order and condition at the aforesaid port of BARCELONA (the Act of God, the King's Enemies, Pirates or Robbers; Restraint of Princes or Rulers; Fire at Sea or on Shore; Accidents from Machinery; Barratry; Negligence or Default of Master, Pilot or Mariners; Vermin; Jettison; and also Accidents of Navigation of every kind excepted; and the ship not being liable to make good loss from and of the cases above accepted) unto Direccion General de Abastelimientos, Minsterio de Hacienda y Economia, Barcelona or to his or their Assigns: Freight and all conditions as per Charter Party including the Negligence Clause. Freight payable by AS AGREED General Average as per York/Antwerp Rules 1924. In Witness whereof, the Master or Agent of the said Ship hath affirmed to TWO Bills of Lading all of this tenor and date; the one of which bills being accomplished the others to stand void. Dated in LIVERPOOL this 10th JANUARY 1938 Weights contents and value unknown and not answerable for leakage or breakage. The vessel is not answerable for any discrepancy between the contents of the packages and description of the same in the Bills of Lading. The Goods to be discharged from the ship as soon as she is ready to unload and into Hulk or Lazaretto if necessary by the Agents of the Owners of the vessel at the Merchants risk and expense. All the terms provisional conditions of the Carriage of Goods by Sea Act 1924 and the Schedule thereto, are to apply to the contract contained in this Bill of Lading and the Carriers are to be entitled to the benefit of all privileges, rights and immunities contained in such Act and the Schedule thereto as if the same were herein specifically set out. If or to the extent that any term of this Bill of lading is repugnant to or inconsistent with anything in such Act or Schedule it shall be void. 292/946/29/45